EU-Japan relations, 1970-2012 : from confrontation to global partnership - Keck, Jörn.; Vanoverbeke, Dimitri; Waldenberger, Franz (London ; New York : Routledge, 2013)
"This book presents a comprehensive overview of EU-Japan relations from 1970 to the present. It charts developments over the period, analyses key specific areas of importance to the relationship, and concludes by assessing how the relationship is likely to develop going forward. Throughout, the book discusses the factors on both sides which motivate the relationship, including Japan's concern to secure markets for its advanced industrial products, and the factors motivating current negotiations for a deeper and more comprehensive economic and cooperative partnership"--
pt. 1. EU-Japan relations from 1970 onward -- pt. 2. Case studies -- pt. 3. Looking forward.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: European Union countries -- Relations -- Japan -- History; Japan -- Relations -- European Union countries -- History; Electronic books